A Re-Examination of Nigerian Media’s Role in Covid-19 Pandemic Awareness Campaign to Mass Audience - Oloyede, I. Bayo (Journal of African films and Diaspora Studies, 2023)
The Covid-19 pandemic has become the most debatable and highly controversial health crisis that has threatened the existence of humanity in recent history. While pandemics are not new in human history, their impact has altered the social structure of the world because they posed a serious threat to public health and the overall stability of systems in society. This paper examines the level of awareness created by Nigerian media during the Covid-19 pandemic. Most especially the flow of information on the Covid-19 pandemic from the government to the people, who most times are majorly dependent on the media. Does information received by the public on Covid-19 influence their adoption of safety protocols? Lastly, to find out if such information has been distorted in any form due to the mass media gatekeeping process and the impact that such may have had on the perception of the populace regarding the graveness of the pandemic. The study adopts a quantitative method using a survey to explore the Covid-19 experienced by Nigerians. Findings show that there are distortions in the dissemination of information owing to the gatekeeping process coupled with some level of non-conformance among highly placed individuals. Records from NCDC show that the percentage of changes in recoveries is considerably higher than the percentage of changes in infections and fatalities during the period under review. It was concluded that the implication of the sustained higher recovery rate over the rate of fatalities is indicative of the possibility of convergence due to some level of perceived awareness the media made during the pandemic.